A study of the services provided by the dining halls in MARA University Of Technology , Samarahan Campus / Lydia Zeta Donald ... [et.al] - Donald, Lydia Zeta; Joseph, Grace Telon; Kemiti, Helen; John, Gordon; Mempani, Mohd Riham Akmal (2004)
This research proposal is a study of the services provided by the dining halls in Mara University of Technology. This research is an important element to determine whether the students of the university are satisfied in the services provided by the dining halls, to find the factors that led to the dissatisfaction of the students and how to overcome the dissatisfaction among the students. This research could be the guidelines for the university’s management to search for the most suitable management to handle the dining hall. The management of the dining hall also can refer to this proposal to fulfill all of the needs and satisfaction of the students. Thus, the management of the dining halls can improve their services based on the research done. By fulfilling the entire requirement needed by the student may encourage the students to have their meal in the dining hall.